High-temperature mechanical property reinforcing material for well cementation cement and preparation method of high-temperature mechanical property reinforcing material

By using a high-temperature mechanical properties enhancement material composed of waste materials, the problem of mechanical properties declining in high-temperature and high-pressure environments is solved, and the high-temperature compressive strength and anti-trapped properties of cement stone are improved, and the advantages of environmental protection and economicality are achieved.

CN119638249AActive Publication Date: 2025-03-18JIAHUA SPECIAL CEMENT
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411876628.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In high temperature and high pressure environment, the mechanical properties of silicate cement stone are difficult to maintain, resulting in unstable cementing and ineffective sealing of the wellbore.

Method used

A high-temperature mechanical properties enhancement material for cementing cement is used. This material consists of waste siliceous shale, biomass slag, coal gasification slag, nanoclay, waste magnesium brick powder, magnesium sterilite powder and waste inorganic insulating materials. Cement stone with high temperature compressive strength is formed through specific mixing and treatment methods.

Benefits of technology

It significantly improves the compressive strength of cement stone in high temperature environments, avoids strength decline, reduces permeability, enhances anti-trappedness, and has the characteristics of green and environmentally friendly and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-temperature mechanical property reinforcing material for well cementation cement and a preparation method of the high-temperature mechanical property reinforcing material. The reinforcing material comprises the following components in percentage by weight: 70-80wt% of a strength stabilizing material A, 5-10wt% of a strength stabilizing material B and 15-20wt% of a crystal form induction material, the strength stabilizing material A is prepared by mixing waste siliceous shale, biomass slag and coal gasification slag according to a mass ratio of (2-3): (1-2): 1. The high-temperature compressive strength of the set cement can be improved, and it can be guaranteed that the compressive strength of the set cement does not decline in the high-temperature environment. By using a large amount of solid wastes as main raw materials, the invention has the characteristics of environmental protection, low cost and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementing materials for oil and gas field development, and in particular to a high-temperature mechanical property enhanced material for cementing cement and a preparation method thereof. Background Art

[0002] In recent years, with the needs of oil and gas field exploration and development, my country's oil and gas production has gradually developed from medium and deep reservoirs to deep and ultra-deep layers. These deep wells and ultra-deep wells have posed new challenges to high-temperature and high-pressure cementing. The harsh downhole environment will cause the strength of cement stone to decline, especially in deep wells where cement stone is exposed to high temperature and high pressure environment for a long time, making it difficult to ensure the long-term effective isolation of the wellbore annulus after a successful cementing. At present, the research on improving the high-temperature mechanical properties of silicate cement stone is mainly to reduce the calcium-silicon ratio of the cement system by using siliceous raw materials. However, studies have shown that simply adding silica sand to cement cannot solve the problem of the decline in the mechanical properties of cement stone in ultra-high temperature environments. Therefore, it is urgent to develop a temperature-resistant reinforcing material for cementing cement to improve the decline in the mechanical properties of the silicate cement system.

[0003] Application No. 201810065622.0 discloses an oil well cement admixture with strength decline resistance and its preparation and application method, wherein the oil well cement admixture mainly comprises 10-35%wt of perlite, 55-85%wt of active silica and 5-20%wt of microsilicon. When the oil well cement admixture is added to the cementing cement slurry system at 10-15 parts by weight of cement, the weight of cement is 100 parts.

[0004] Application No. 202011032805.6 discloses a high-temperature cementing cement and its preparation method and application. The high-temperature cementing cement contains the following raw materials in percentage by mass: 69-72% cement raw materials; 28-31% quartz sand; the cement raw materials are composed of G-grade oil well cement and nuclear power cement in a mass ratio of 4:6-5:5.

[0005] The above technologies can only meet the strength performance of cement paste in high temperature environment. It cannot meet the performance requirements of cement paste at higher temperatures. Therefore, it is particularly important to develop a temperature-resistant reinforcement material suitable for ensuring that the strength of cement does not decline in ultra-high temperature environment. Summary of the invention

[0006] The object of the present invention is to provide a high temperature mechanical property enhancing material for cementing cement and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted in the present invention is as follows: In one aspect, the present invention provides a high temperature mechanical property enhancing material for cementing cement, comprising the following raw materials in weight percentage: Strength stable material A: 70~80wt%; Strength-stabilized material B: 5~10wt%; Crystal inducing material: 15~20wt%; The strength stabilizing material A is prepared by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of (2-3):(1-2):1.

[0008] Furthermore, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form powder, and the powder particle size is 600 mesh.

[0009] Furthermore, the SiO2 content of the biomass slag is ≥65wt%, and the Al2O3 content is ≥15wt%. The biomass slag is dried and ground to form a powder with a particle size of 600 mesh.

[0010] Furthermore, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 mesh.

[0011] Furthermore, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2.

[0012] Furthermore, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%; the MgO content of the waste magnesium brick powder is ≥90wt%, and the powder particle size is 325 mesh; the SiO2 content of the forsterite powder is ≥40wt%, and the MgO content is ≥50wt%, and the powder particle size is <600 mesh.

[0013] Furthermore, the crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards.

[0014] Furthermore, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed to form powder, and the powder particle size is less than 10 μm.

[0015] On the other hand, the present invention provides a method for preparing a high temperature mechanical property enhancing material for cementing cement, comprising the following steps: S1. Mix the strength stabilizing material A and the crystal inducing material of each mass and place them in a sealed stirring tank, add a solvent, and stir at room temperature to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. Powder A and strength stabilizing material B are evenly mixed by pneumatic means to obtain the high temperature mechanical property enhancing material for cementing cement.

[0016] Furthermore, in S1, anhydrous ethanol is used as the solvent, the liquid-to-solid ratio is 5:1, and the stirring time at room temperature is 24 to 48 hours.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The high temperature mechanical property enhancing material for cementing cement of the present invention can improve the high temperature compressive strength of cement stone and ensure that the compressive strength of cement stone does not decline under high temperature environment. The present invention uses a large amount of solid waste as the main raw material, and has the characteristics of green environmental protection, low cost and excellent performance.

[0018] 2. The high-temperature mechanical property enhancing material for cementing cement of the present invention adopts solid waste whose main components are SiO2 and Al2O3, thereby ensuring the calcium-silicon ratio and high-temperature strength of the cement slurry system and greatly reducing the use of silica sand.

[0019] 3. The strength stabilizing material B of the present invention and the strength stabilizing material A jointly reduce the calcium-silicon ratio of the cement system, and can also form Mg(OH)2 during the high-temperature hydration process of cement, so that the cement paste has a certain expansibility; in addition, the filling and heterogeneous nucleation effect of nano-clay can refine the pore structure, and the synergistic effect with the forsterite powder with excellent temperature resistance greatly reduces the permeability of the cement paste, enhances the density and interface bonding ability of the cement paste, and thus improves the anti-channeling ability and mechanical properties of the cement paste.

[0020] 4. The crystal inducing material of the present invention can be used as a seed material in the cement hydration process to induce the cement hydration product to quickly crystallize at high temperature to form more xonotlite and tobermorite, thereby improving the high temperature resistance of cement paste and avoiding the decline of cement paste strength.

[0021] 5. The present invention utilizes the characteristics of strength-stabilizing material A, which is porous and has a large specific surface area, to load the crystal-inducing material inside and on the surface of the pores of strength-stabilizing material A. When the cement hydration product reacts with active ions such as silicon and aluminum released by strength-stabilizing material A and strength-stabilizing material B, the presence of the crystal-inducing material not only greatly accelerates the formation of xonotlite and tobermorite, but also induces the formation of aluminosilicate minerals and aluminum substitutes, further enhancing the high-temperature resistance of cement stone and avoiding the decline in strength. In addition, the small amount of carbon powder present in strength-stabilizing material A can not only synergize with strength-stabilizing material B to fill the pores and reduce the porosity, but also provide crystallization points for the hydration products and promote hydration. Based on the principle of synergistic effect, the high-temperature mechanical performance enhancing material for cementing cement mixed in a certain proportion has the characteristics of high temperature resistance, inhibition of strength decline, reduced permeability, improved anti-channeling, low cost, and green environmental protection. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] The following examples of the present invention all prepare cement slurries according to GB / T19139 standard, wherein the G-grade oil well cement is provided by Jiahua Special Cement Co., Ltd. Example

[0024] As a preferred embodiment of the present invention, the composition of the high temperature mechanical property enhancing material for cementing cement in this embodiment is shown in Table 1.

[0025] Table 1

[0026] In this embodiment, the strength-stabilizing material A is formed by mixing waste siliceous shale, biomass slag, and coal gasification slag in a mass ratio of 2:1:1.

[0027] In this embodiment, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder, and forsterite powder in a mass ratio of 1:1:2.

[0028] In this embodiment, the crystal inducing material is insulation brick waste.

[0029] In this embodiment, the raw materials are weighed according to Table 1, and the preparation method of the high temperature mechanical property enhancing material for cementing cement is as follows: S1. Mix the strength stabilizing material A and the crystal inducing material and place them in a sealed stirring tank, use anhydrous ethanol as solvent, with a liquid-to-solid ratio of 5:1, and stir at room temperature for 48 hours to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. Evenly mix the powder A and the strength stabilizing material B by a pneumatic mixing device to obtain a high temperature mechanical property enhancing material 1# for cementing cement.

[0030] Example 2 As a preferred embodiment of the present invention, the composition of the high temperature mechanical property enhancing material for cementing cement in this embodiment is shown in Table 2.

[0031] Table 2

[0032] In this embodiment, the strength-stabilizing material A is formed by mixing waste siliceous shale, biomass slag, and coal gasification slag in a mass ratio of 2:1:1.

[0033] In this embodiment, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder, and forsterite powder in a mass ratio of 1:1:2.

[0034] In this embodiment, the crystal inducing material is insulation brick waste.

[0035] In this embodiment, the raw materials are weighed according to Table 2, and the preparation method of the high temperature mechanical property enhancing material for cementing cement is as follows: S1. Mix the strength stabilizing material A and the crystal inducing material and place them in a sealed stirring tank, use anhydrous ethanol as solvent, with a liquid-to-solid ratio of 5:1, and stir at room temperature for 48 hours to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. The powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a high temperature mechanical property enhancing material 2# for cementing cement.

[0036] Example 3 As a preferred embodiment of the present invention, the composition of the high temperature mechanical property enhancing material for cementing cement in this embodiment is shown in Table 3.

[0037] Table 3

[0038] In this embodiment, the strength-stabilizing material A is formed by mixing waste siliceous shale, biomass slag, and coal gasification slag in a mass ratio of 2:1:1.

[0039] In this embodiment, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder, and forsterite powder in a mass ratio of 1:1:2.

[0040] In this embodiment, the crystal inducing material is insulation board waste.

[0041] In this embodiment, the raw materials are weighed according to Table 3, and the preparation method of the high temperature mechanical property enhancing material for cementing cement is as follows: S1. Mix the strength stabilizing material A and the crystal inducing material and place them in a sealed stirring tank, use anhydrous ethanol as solvent, with a liquid-to-solid ratio of 5:1, and stir at room temperature for 48 hours to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. The powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a high temperature mechanical property enhancing material 3# for cementing cement.

[0042] Example 4 As a preferred embodiment of the present invention, the composition of the high temperature mechanical property enhancing material for cementing cement in this embodiment is shown in Table 4.

[0043] Table 4

[0044] In this embodiment, the strength-stabilizing material A is formed by mixing waste siliceous shale, biomass slag, and coal gasification slag in a mass ratio of 3:1:1.

[0045] In this embodiment, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder, and forsterite powder in a mass ratio of 1:1:2.

[0046] In this embodiment, the crystal inducing material is insulation board waste.

[0047] In this embodiment, the raw materials are weighed according to Table 4, and the preparation method of the high temperature mechanical property enhancing material for cementing cement is as follows: S1. Mix the strength stabilizing material A and the crystal inducing material and place them in a sealed stirring tank, use anhydrous ethanol as solvent, with a liquid-to-solid ratio of 5:1, and stir at room temperature for 36 hours to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. The powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a high temperature mechanical property enhancing material 4# for cementing cement.

[0048] Example 5 As a preferred embodiment of the present invention, the composition of the high temperature mechanical property enhancing material for cementing cement in this embodiment is shown in Table 5.

[0049] Table 5

[0050] In this embodiment, the strength-stabilizing material A is formed by mixing waste siliceous shale, biomass slag, and coal gasification slag in a mass ratio of 2:2:1.

[0051] In this embodiment, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder, and forsterite powder in a mass ratio of 1:1:2.

[0052] In this embodiment, the crystal inducing material is insulation board waste.

[0053] In this embodiment, the raw materials are weighed according to Table 5, and the preparation method of the high temperature mechanical property enhancing material for cementing cement is as follows: S1. Mix the strength stabilizing material A and the crystal inducing material and place them in a sealed stirring tank, use anhydrous ethanol as solvent, with a liquid-to-solid ratio of 5:1, and stir at room temperature for 24 hours to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. The powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a high temperature mechanical property enhancing material 5# for cementing cement.

[0054] Comparative Example 1 This comparative example is to add 30wt% of 300 mesh quartz sand into G-grade oil well cement.

[0055] Comparative Example 2 This comparative example is the same as Example 1 except that the strength stabilizing material A does not contain coal gasification slag, and a reinforced material 1* is obtained.

[0056] Comparative Example 3 This comparative example is the same as Example 1 except that the strength stabilizing material B does not contain forsterite powder, and a reinforcing material 2* is obtained.

[0057] Comparative Example 4 This comparative example is the same as Example 1 except that strength stabilizer material A is used to replace the crystal form inducing material, that is, no crystal form inducing material is contained, and the rest is the same as Example 1 to obtain a reinforced material 3*.

[0058] Test Case According to GB / T 19139 standard, cement slurry was prepared with a water-cement ratio of 0.44. The amount of reinforcing materials in Examples 1 to 5 of the present invention and Comparative Examples 2 to 4 was 30wt% (the amount of each reinforcing material added was 30wt% of the mass of G-grade oil well cement) to prepare cement slurry. At the same time, Comparative Example 1 was used as the control cement slurry. Each cement slurry was poured into a copper mold and then placed in a high-temperature curing kettle for curing. The curing temperature was 250°C, and the curing period was 2d, 7d, and 28d. The compressive strength change was detected, and the cement stone permeability was tested. The test results are shown in Table 6.

[0059] Table 6

[0060] It can be seen from the data in Table 6 that, compared with Comparative Example 1, the cement paste formed by Examples 1 to 5 has high strength and no decline after a certain age of curing, and the permeability is greatly reduced. This shows that the present invention can effectively inhibit the decline of cement paste strength, reduce porosity, and improve the compressive strength of cement paste. The results of Comparative Examples 2 to 4 show that there is a synergistic effect between the components in the present invention, and the lack of any one of them cannot achieve the expected effect of the present invention.

[0061] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A high temperature mechanical property enhancing material for cementing cement, characterized in that: The following raw materials are included in weight percentage: Strength stable material A: 70~80wt%; Strength-stabilized material B: 5~10wt%; Crystal inducing material: 15~20wt%; The strength stabilizing material A is prepared by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of (2-3):(1-2):

1.

2. The high temperature mechanical properties enhancing material for cementing cement according to claim 1, characterized in that: The SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form powder, and the powder particle size is 600 mesh.

3. The high temperature mechanical property enhancing material for cementing cement according to claim 1, characterized in that: The biomass slag has a SiO2 content of ≥65wt%, an Al2O3 content of ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 meshes.

4. The high temperature mechanical property enhancing material for cementing cement according to claim 1, characterized in that: The coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 meshes.

5. The high temperature mechanical property enhancing material for cementing cement according to claim 1, characterized in that: The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:

2.

6. The high temperature mechanical property enhancing material for cementing cement according to claim 5, characterized in that: The SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%; the MgO content of the waste magnesium brick powder is ≥90wt%, and the powder particle size is 325 mesh; the SiO2 content of the forsterite powder is ≥40wt%, and the MgO content is ≥50wt%, and the powder particle size is <600 mesh.

7. The high temperature mechanical property enhancing material for cementing cement according to claim 1, characterized in that: The crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards.

8. The high temperature mechanical property enhancing material for cementing cement according to claim 7, characterized in that: The components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed to form powder, and the powder particle size is less than 10 μm.

9. The method for preparing a high temperature mechanical property enhancing material for cementing cement according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix the strength stabilizing material A and the crystal inducing material of each mass and place them in a sealed stirring tank, add a solvent, and stir at room temperature to form slurry A; S2, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S3. Powder A and strength stabilizing material B are evenly mixed by pneumatic means to obtain the high temperature mechanical property enhancing material for cementing cement.

10. The method for preparing a high temperature mechanical property enhancing material for cementing cement according to claim 9, characterized in that: In S1, anhydrous ethanol is used as the solvent, the liquid-to-solid ratio is 5:1, and the stirring time at room temperature is 24 to 48 hours.

Citation Information

Patent Citations

  • Anti-strength-retrogression oil well cement admixture and preparation and application methods

    CN110066648A

  • High-temperature well cementation cement as well as preparation method and application thereof

    CN112094060A

  • Well cementation oil well cement composition and preparation method thereof

    CN111362656A

  • High-temperature strength decline resistant oil well cement slurry system

    CN115304317A

  • High-temperature strength decline resistant material for well cementation and preparation method of high-temperature strength decline resistant material

    CN115353868A